Can exercise help regulate blood pressure and improve functional capacity of older women with hypertension against the deleterious effects of physical inactivity? - Leitão, Hugo (2021)
Background: Sedentarism and inactivity are risk factors for the development of hyperten sion. Thus, the prevention of the natural process of biological and physiological aging of older women through physical exercise results in higher benefits in preventing cardiovascular diseases and can be a key factor for its treatment. Multicomponent exercise (METP) is a training method that may help older women with hypertension by improving their quality of life and their response to treatment. Methods: Twenty-eight older Caucasian women with hypertension (66.7 ± 5.3 years, 1.59 ± 0.11 m) performed a supervised METP program of nine months followed by three months of detraining (DT), and seventeen older women (68.2 ± 4.7 years, 1.57 ± 0.16 cm) with hypertension maintained their daily routine, without exercise. Blood pressure (BP), resting heart rate, and functional capacity (FC) were evaluated at the beginning and at the end of the program, and after three months of DT. Results: The ME program improved (p < 0.05) systolic BP (−5.37%), diastolic BP (−5.67%), resting heart rate (−7.8%), agility (9.8%), lower body strength (27.8%), upper body strength (10.0%), and cardiorespiratory capacity (8.6%). BP and FC deteriorated after the DT period (p < 0.05). Conclusion: Nine months of multicomponent exercise were sufficient to improve functional capacity and promote benefits in blood pressure, although was not sufficient to allow BP to reach the normal values of older women. The three month DT period without exercise caused the reversal of BP improvements but maintained the functional capacity of older women.